Implementasi Algoritma Genetika untuk Penjadwalan Instruktur Training ICT UIN Sunan Kalijaga - Niki Min Hidayati Robbi; Nurochman Nurochman (UIN Sunan Kalijaga Yogyakarta, 2017)
ICT training instructor scheduling involves components such as the division of the day, sessions, classroom, and availability time of instructor which is different every day. One of the methods of artificial intelligence that is suitable for case scheduling is a Genetic Algorithm. Genetic algorithm succesfully impelemented for scheduling ICT training instructor with the parameter crossover probability (Pc) 0.4, the probability of mutation (Pm) 0.1, and the total population of 30 individuals. The best fitness value is 0.9523 with a 1 value error on constraint division of classrooms that weighs 0,05. Keywords: Genetic Algorithm, Scheduling